2007
DOI: 10.1007/s10531-007-9188-0
|View full text |Cite
|
Sign up to set email alerts
|

Cocoa farms in the Mount Cameroon region: biological and cultural diversity in local livelihoods

Abstract: A study was undertaken around Mt Cameroon to examine the role of biological and cultural diversity in the livelihood strategies of indigenous villagers and migrants to the region. Surveys of resources consumed and sold by 118 households were undertaken in five villages over the course of 1 year, the perspectives and practices of cocoa farmers documented, and useful tree species retained or planted on six cocoa farms mapped. Cocoa farms in this region generate more significant benefits for biodiversity conserva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
38
1
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(41 citation statements)
references
References 9 publications
(9 reference statements)
1
38
1
1
Order By: Relevance
“…Des inventaires des arbres de dbh supérieurs ou égal à 5 cm ont permis de recenser aussi plus d'espèces (105 espèces) au Sud du Brésil (Rolim et Chiarello, 2004). Cependant les plantations cacaoyères de Lakota ont des richesses comparables aux résultats des études menées au Cameroun par Jeofack et al (2013) avec 59 espèces et Laird et al (2007) avec 50 espèces. Au Nigeria, Oke et Olatiilu (2011) ont obtenu une richesse de 76 espèces dans les plantations cacaoyères de la réserve forestière de Ogbese.…”
Section: Analyse Des Donnéesunclassified
“…Des inventaires des arbres de dbh supérieurs ou égal à 5 cm ont permis de recenser aussi plus d'espèces (105 espèces) au Sud du Brésil (Rolim et Chiarello, 2004). Cependant les plantations cacaoyères de Lakota ont des richesses comparables aux résultats des études menées au Cameroun par Jeofack et al (2013) avec 59 espèces et Laird et al (2007) avec 50 espèces. Au Nigeria, Oke et Olatiilu (2011) ont obtenu une richesse de 76 espèces dans les plantations cacaoyères de la réserve forestière de Ogbese.…”
Section: Analyse Des Donnéesunclassified
“…Agroforestry systems, where crops such as cacao are grown under the canopy of shade forest trees, are considered as an alternative to conventional agriculture in the sense that they provide many environmental ecosystemic services such as: enhancing functional biodiversity (Laird et al 2007; Oke and Odebiyi (Kotto-Same et al 1997;Somarriba et al 2013;Sonwa et al 2009;Zapfack et al 2002) soil fertility and thermal regulation (Anglaaere et al 2011;Gockowski and Sonwa 2011;Gockowski et al 2010;Nair 2012). Cocoa-based agroforestry systems (CAFS) are drought resistant and serve as weed and pest biological control (Tscharntke et al 2011) and they can mimic the structural and functional elements of the forest (Gockowski et al 2005).…”
Section: Introductionmentioning
confidence: 99%
“…These types of agroforestry systems are currently considered to be of high economic and environmental value (Duguma et al 2001;Johns 1999;Rice and Greenberg 2000;Schroth and Harvey 2007). Other studies in Cameroon or in Ghana have revealed the potential interest of such agroforestry systems for carbon sequestration and management of soil organic matter (Bisseleua et al 2008;Kotto-Same et al 1997;Laird et al 2007). But few studies have been conducted on soil fertility trends in cocoa agroforests, in comparison with other ecosystems (Hartemink 2005;Isaac et al 2007).…”
Section: Introductionmentioning
confidence: 99%